2021
DOI: 10.31018/jans.v13i4.2999
|View full text |Cite
|
Sign up to set email alerts
|

Biorational management of maize fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) using Bacillus thuringiensis (Berliner) enriched with chemical additives

Abstract: An invasive pest, fall armyworm, Spodoptera frugiperda (J.E.Smith) (Lepidoptera: Noctuidae) attacks maize at every stage of development, from seedling emergence up to cob formation. Early instar larvae were seen mostly on leaves of maize with characteristics pin or shot hole symptoms. Later instar larvae were confined to deep whorls, leaving typically ragged like appearance and fed on the reproductive stage of the crop especially tassels and developing cobs resulting in quality and quantity loss of maize produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Zhang, et al (2013) pointed out that many inorganic salts can increase the activity of Bacillus thuringiensis against P. xylostella larvae at different levels when combined with them, as he found calcium salts (calcium hydroxide, calcium chloride, calcium carbonate and calcium sulfate) have the preference increasing the activity of B. thuringiensis, followed by some other salts such as Sodium carbonate, potassium hydroxide and sodium acetate. Priyanka, et al (2021) indicated that treatments of B. thuringiensis in addition to inorganic salts were significantly effective against fall armyworm larvae compared with B. thuringiensis alone.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang, et al (2013) pointed out that many inorganic salts can increase the activity of Bacillus thuringiensis against P. xylostella larvae at different levels when combined with them, as he found calcium salts (calcium hydroxide, calcium chloride, calcium carbonate and calcium sulfate) have the preference increasing the activity of B. thuringiensis, followed by some other salts such as Sodium carbonate, potassium hydroxide and sodium acetate. Priyanka, et al (2021) indicated that treatments of B. thuringiensis in addition to inorganic salts were significantly effective against fall armyworm larvae compared with B. thuringiensis alone.…”
Section: Resultsmentioning
confidence: 99%